2019
DOI: 10.1002/ece3.5241
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affect the distribution of two Epichloë fungal endophyte species inhabiting a common host grove bluegrass (Poa alsodes)

Abstract: Aim The endophyte Epichloë alsodes, with known insecticidal properties, is found in a majority of Poa alsodes populations across a latitudinal gradient from North Carolina to New York. A second endophyte, E. schardlii var. pennsylvanica, with known insect‐deterring effects, is limited to a few populations in Pennsylvania. We explored whether such disparate differences in distributions could be explained by selection from biotic and abiotic environmental factors. Location Along the Appalachian Mountains from No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 73 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…Hybrids are likely to contain more genetic variation, which may lead to improved adaptation to biotic and abiotic stresses of their host plants [ 10 , 29 , 30 , 56 , 61 ]. There is also a general hypothesis that interspecific hybridisation provides greater genetic variation and hence, a wider adaptation range in stressful environments than intraspecific hybridisation [ 56 , 62 ]. However, when comparing hybrid and non-hybrid Epichloë strains on controlled environments, there is no evidence of niche expansion of Epichloë hybrid-infected plants [ 63 ].…”
Section: Epichloë Endophytesmentioning
confidence: 99%
“…Hybrids are likely to contain more genetic variation, which may lead to improved adaptation to biotic and abiotic stresses of their host plants [ 10 , 29 , 30 , 56 , 61 ]. There is also a general hypothesis that interspecific hybridisation provides greater genetic variation and hence, a wider adaptation range in stressful environments than intraspecific hybridisation [ 56 , 62 ]. However, when comparing hybrid and non-hybrid Epichloë strains on controlled environments, there is no evidence of niche expansion of Epichloë hybrid-infected plants [ 63 ].…”
Section: Epichloë Endophytesmentioning
confidence: 99%
“…Comparing the performance of endophyte-colonized plants with endophyte-free plants has been the most common experimental approach to understand the mechanisms influencing the endophyte incidence in plant populations. Very few studies have focused on underlying factors that affect the transmission process and persistence of the endophyte (Gundel et al, 2008;Gundel, Rudgers, & Ghersa, 2011;Ravel et al, 1997;Shymanovich & Faeth, 2019). Inefficiencies in the vertical transmission process mean that a host plant can produce a variable proportion of both endophyte-colonized and endophyte-free offspring (Afkhami & Rudgers, 2008;Gibert & Hazard, 2013;Gundel, Rudgers, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that the presence of fungal endophytes affected germination parameters of B. auleticus seeds in response to temperature and water availability but more importantly, these effects depended on the population origin and seemed to be related with the environmental characteristics of collection site. Considering that endophyte‐specific effects may result from partners' co‐adaptation to the prevailing environmental conditions (Shymanovich & Faeth, 2019), our results suggest that these differential effects associated to population origin and site of collection are the expression of an endophyte‐mediated ecotypic response.…”
Section: Discussionmentioning
confidence: 72%
“…For several indigenous grasses from Argentina (i.e., B. auleticus , Bromus pictus ) it has been reported that endophytes can promote plant growth (Iannone & Cabral, 2006; Iannone, Pinget, et al, 2012; Novas et al, 2003), mycorrhizal colonisation (Novas et al, 2005, 2009, 2011; Vignale et al, 2016, 2018), and to confer resistance to pathogens in B. auleticus (Iannone et al, 2017; Vignale et al, 2013). Despite these overall benefits, it is unclear if endophyte mediated effects on grasses of South America can vary in different populations and contribute to plant adaptation to the local environmental conditions as reported in Festuca arizonica (Sullivan & Faeth, 2008) and Poa alsodes (Shymanovich & Faeth, 2019).…”
Section: Introductionmentioning
confidence: 99%